2009
DOI: 10.1111/j.1471-6712.2007.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of follow‐up in intensive care: patients’ perspective

Abstract: The growing understanding of correlations between experiences and memories from a period of intensive care treatment and complaints of mental character has led to the development of various patient follow-up offers. Little, however, is known about what follow-up may mean to patients. The aim of this study was to explore the meaning of patients' lived experience of being followed-up in a programme consisting of patient diaries, post-intensive care unit (ICU) conversations and visits back to the ICU. Field notes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 38 publications
2
72
0
12
Order By: Relevance
“…The purpose is to help the patient to remember their time in the ICU and for the family to get answers to any questions they have. The opportunity to visit the room where the patient was cared for has been shown to help the patients to anchor their dreams in reality (Bäckman et al, 2010;Egerod and Christensen, 2009;Gjengedal et al, 2010;Griffiths et al, 2009;Knowles and Tarrier, 2009;Storli and Lind, 2009;Åkerman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose is to help the patient to remember their time in the ICU and for the family to get answers to any questions they have. The opportunity to visit the room where the patient was cared for has been shown to help the patients to anchor their dreams in reality (Bäckman et al, 2010;Egerod and Christensen, 2009;Gjengedal et al, 2010;Griffiths et al, 2009;Knowles and Tarrier, 2009;Storli and Lind, 2009;Åkerman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The findings also highlight the experiences of emotional difficulty by some, for example, nervousness and insecurity involved with returning to the ICU. Storli and Lind (2009) support this, and assert that a return visit to the intensive care room in which they were cared for, can cause feelings of gratitude about having survived this event, and assist with things falling into place. This visit can also make the experience more meaningful through the verbalization of one's feelings and the expression of wanting to face the emotionally difficult aspects at one's own pace.…”
Section: Discussionmentioning
confidence: 94%
“…It is hoped that this information will clarify and address any questions relating to the patients particular memories, nightmares, and any remaining difficulties from their time spent in the ICU. This can also serve as a valuable knowledge tool for ICU staff (Samuelson and Corrigan, 2009;Storli and Lind, 2009). Therefore, the aim of the study was to describe how ICU patients, experience a follow-up session.…”
Section: Introductionmentioning
confidence: 99%
“…Observational [22,38,[40][41][42][43], prospective cohort with a retrospective reference group [39] , timeseries [1] and qualitative [52,[54][55][56][57] studies have reported the success and importance of patient diaries in the clinical setting. Our review has demonstrated the paucity of randomized controlled trials evaluating patient diaries.…”
Section: Discussionmentioning
confidence: 99%